Ahmad al-Mansur Islamic visionary - Smith, Richard L. (New York Pearson Longman, 2006)
This new entry into the Longman World Biography series examines a leading statesman who guided a key country during a pivotal time in history. Al-Mansur was a man of contradictions whose policies combined a vision of the future with a longing for the past; by building one state, he destroyed another.
Includes bibliographical references and index.
Keywords: Aḥmad al-Manṣūr, Sultan of Morocco, 1549-1603.